Developing a high-throughput screening method for threonine overproduction based on an artificial promoter. Issue 1 (December 2015) - Liu, Ya'nan; Li, Qinggang; Zheng, Ping; Zhang, Zhidan; Liu, Yongfei; Sun, Cunmin; Cao, Guoqiang; Zhou, Wenjuan; Wang, Xiaowei; Zhang, Dawei; Zhang, Tongcun; Sun, Jibin; et al.
Abstract Background l -Threonine is an important amino acid for animal feed. Though the industrial fermentation technology of threonine achieved a very high level, there is still significant room to further improve the industrial strains. The biosensor-based high-throughput screening (HTS) technology has demonstrated its powerful applications. Unfortunately, for most of valuable fine chemicals such as threonine, a HTS system has not been established mainly due to the absence of a suitable biosensor. In this study, we developed a HTS method to gain high-yielding threonine-producing strains. Results Novel threonine sensing promoters including cysJp and cysHp were discovered by proteomic analyses ofEscherichia coli in response to extracellular threonine challenges. The HTS method was constructed using a device composed of the fused cysJp and cysHp as a promoter and a linked enhanced green fluorescent protein gene as a reporter. More than 400 strains were selected with fluorescence activated cell sorting technology from a library of 20 million mutants and tested within 1 week. Thirty-four mutants have higher productivities than the starting industrial producer. One mutant produced 17.95 % more threonine in a 5-L jar fermenter. Conclusions This method should play a functional role for continuous improvement of threonine industry. Additionally, the threonine sensor construction using promoters obtained by proteomics analyses is so convenient that it would be easily extended to develop HTS models for other biochemicals.